Estudio de factibilidad para la creación de una aplicación web empleando robocall, códigos qr y analítica de datos para el seguimiento académico de los estudiantes de la “Unidad Educativa Cardenal Spinola” de la cuidad de Quito sector Solanda - Martillo Pacheco, Daniel Darwin (2021)
This study is based on the study and analysis of technical, operational and economic feasibility to determine the viability of creating a web application using robocall, QR code and data analysis for the academic monitoring of students of the Cardenal Spínola Educational Unit of the city of Quito in the Solanda sector. Given that, said institution has problems in academic monitoring activities such as records stored in physical and digital databases (Excel spreadsheets), loss of records, they do not have applications for the identification of regressive or progressive performance, communication through of notes registered in agendas, slowness in instant access to student information, among others. Therefore, students face possible serious failures such as low academic performance and even low self-esteem, staying in supplementary, remedial, thank you exams or loss of the year given that the institution does not have technology according to the previous challenges such as a web application using Robocall technology, QR codes and data analytics to stay at the forefront of 21st century technologies. For this, the methodology that was used in the present case study is the field methodology together with two qualitative methods that helped to know in a specific and efficient way the problems currently existing in the Educational Unit along with its technique the interview carried out with the coordinator Gabriel Leave the institution through the instrument the interview questionnaire and the quantitative one that will get to know in a precise and exact way the opinion of the teachers and parents or the representative through the survey technique through the survey questionnaire.